A multilevel analysis of social capital and smoking behavior in Seoul, South Korea. - Han, Sehee (Journal of Substance Use, 2018)
Objective: This study examined the association between social capital and smoking. Methods: A cross-sectional survey was conducted from December 2010 to April 2011 in Seoul, South Korea. In total, 4,734 respondents within 25 administrative-areas were analyzed. Multilevel logistic regression analysis was used. Results: Various dimensions of social capital at the individual level were positively or negatively associated with smoking at the individual level. Network resource was positively associated with smoking (OR = 1.17; 95% CI = 1.03, 1.33). Organizational participation was negatively associated with smoking (OR = 0.81; 95% CI = 0.67, 0.98). Trust was negatively associated with smoking (OR = 0.91; 95% CI = 0.88, 0.94). However, none of the area-level social capital variables were associated with smoking. Conclusions: Findings indicate that social capital has not only a bright side but a dark side as well. The present study provides evidence that the higher levels of social capital are not always good for individuals’ health behavior.